2015
DOI: 10.5397/cise.2015.18.3.128
|View full text |Cite
|
Sign up to set email alerts
|

PHILOS Plate Osteosynthesis in Metaphyseal Fractures of the Distal Humerus through an Anterolateral Approach

Abstract: Background: We described a surgical method for osteosynthesis and reported the resultant strength after application of a PHILOS plate through the anterolateral approach for the treatment of fractures of the distal humerus. Methods: Between February 2010 and March 2012, open reduction and internal fixation operations with the PHILOS plate for treatment of fracture of the distal humerus were performed on a total of nine patients (five men, four women). The mean age was 40.8 years (range, 24-50 years), and the av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…In line with our findings, retrospective studies of the PHILOS alone or in comparison with the EADHP have shown satisfactory clinical and radiologic outcomes 6 , 22 , 28 . In a biomechanical study using cadavers, Lim et al 18 reported that anterior plating with a modified PHILOS showed a fixation and biomechanical performance comparable to those of posterior plating with the EADHP.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with our findings, retrospective studies of the PHILOS alone or in comparison with the EADHP have shown satisfactory clinical and radiologic outcomes 6 , 22 , 28 . In a biomechanical study using cadavers, Lim et al 18 reported that anterior plating with a modified PHILOS showed a fixation and biomechanical performance comparable to those of posterior plating with the EADHP.…”
Section: Discussionsupporting
confidence: 90%
“…As a result, we determined the fixation range and state of the PHILOS. In previous studies, anterior plating was performed with the modified PHILOS 22 , 28 , and a comparison was made between posterior plating with the EADHP and anterior plating with the modified PHILOS 6 . Biomechanical study using cadavers to compare posterior plating with the EADHP and anterior plating with the modified PHILOS have also been conducted 18 .…”
Section: Discussionmentioning
confidence: 99%
“…This locking plate does not use the posterolateral column of the distal humerus and seems to be less affected by protrusion; however, whether the biomechanical properties of the plate are comparable to conventional EADHPs should be investigated. As another alternative, a locking compression plate used for the proximal humerus was suggested via an anterolateral approach [19,20]. A previous biomechanical study showed that modified use of a proximal humeral locking plate has comparable mechanical stability com-Fig.…”
Section: Discussionmentioning
confidence: 99%
“…But sometimes they are being used other than where they are supposed to be placed. The report 'PHILOS Plate Osteosynthesis in Metaphyseal Fractures of the Distal Humerus through an Anterolateral Approach' by Park et al 1) is one of the good examples, where the authors placed PHILOS plates on distal humerus fractures, which was designed originally for proximal humerus fractures. The authors claim that the wellconformed anatomical framework between the plate and the anterior surface of distal humerus make it possible to fix the fracture suitably.…”
mentioning
confidence: 99%